Tradeoffs and complementarities in the adoption of improved seeds, fertilizer, and natural resource management technologies in Kenya - Priscilla Wainaina; Songporne Tongruksawattana; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
There is widespread consensus that agricultural technology has an important role to play for poverty reduction and sustainable development. There is less consensus, however, about the types of technologies that are best suited for smallholder farmers in Africa. While some consider natural resource management (NRM) technologies as most appropriate, others propagate input intensification with a stronger role of the private sector. In the public debate, the two strategies are often perceived as incompatible. Most existing adoption studies focus on individual technologies, so that comparisons across technologies in the same context are not easily possible. We use representative data from maize-producing households in Kenya and a multivariate probit model to analyze the adoption of different types of technologies simultaneously. Results indicate that NRM technologies and strategies that build on external inputs are not incompatible. Interesting complementarities exist, which are not yet sufficiently exploited, because many organizations promote either one type of technology or the other, but rarely a combination of both.
http://purl.umn.edu/189914
Keywords: O13; O33; Q12; Q16; 330; technology adoption; maize; small farms; sustainable agriculture; Africa